STRATEGI PEMASARAN DALAM MENINNGKATKAN VOLUME PENJUALAN PADA TOKO BROWNIES CINTA AGEN CAWAS KLATEN - Nur Qori Yogi Setiana; Erry Setyo Prabowo; Suin Lestari (Fenomena, 2025)
Competition between businesses is currently influenced by changes in market conditions. Marketing activities have an effect on increasing sales volume. Strategies that can be used by companies include product strategies, promotions, prices and place strategies. Brownies Cinta is a snack business that already has several sales agents on the island of Java, one of which is an agent in Cawas District. This research aims to determine the marketing strategy carried out by the Cinta Brownies Shop, Cawas Klaten Agent, in increasing sales volume. The method used in this research is qualitative methods. The results of this research are that the product strategy of Toko Brownies Cinta Agen Cawas Klaten provides good quality and taste, the price strategy is to provide affordable prices, the location strategy is to build a strategic business on the side of the main road, namely on Jl. Pedan-Cawas No. 12, Dusun I, Plosowangi, Cawas District, Klaten Regency and promotional strategies using social media, namely Facebook, Instagram, Go Food and WhatsApp. The conclusion of this research is that the Cinta Brownies Shop, Agent Cawas Klaten, in marketing its products uses a 4P marketing mix consisting of Product, Price, Place and Promotion. From these four strategies, it can be seen that the 4P variables are used is very influential in increasing sales volume.